2005
DOI: 10.1164/rccm.200411-1537oc
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Reverses Airflow Obstruction in Established Bronchiolitis Obliterans Syndrome

Abstract: This case series confirms the benefit of azithromycin in not only halting, but reversing the declining lung function seen in patients with BOS. This benefit appears to be maintained over time. Low-dose macrolides offer a new and exciting therapeutic strategy for the treatment of progressive BOS, and further clinical and translational mechanistic studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(148 citation statements)
references
References 37 publications
5
132
1
10
Order By: Relevance
“…The strategy in our service was to administer antibiotics to patients during the acute pulmonary phase (fever, increased cough, changes in viscosity, secretion amount or color). Some recent studies analyzed the role of azithromycin in the treatment of BO and showed that it reduces inflammatory markers in the bronchoalveolar lavage (BAL) and even improves pulmonary function (15,24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…The strategy in our service was to administer antibiotics to patients during the acute pulmonary phase (fever, increased cough, changes in viscosity, secretion amount or color). Some recent studies analyzed the role of azithromycin in the treatment of BO and showed that it reduces inflammatory markers in the bronchoalveolar lavage (BAL) and even improves pulmonary function (15,24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of azithromycin in a randomized controlled trial has been shown to slow the progression of CLAD, potentially through its anti-inflammatory, antibiotic, or promotility effects, but the exact mechanism is unclear (Yates et al 2005;Murphy et al 2008;Vos et al 2011). Switching classes of immunosuppression may be of some benefit in slowing progression of the disease, but no therapy has yet been shown to reverse the disease process.…”
Section: Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…Nesses pacientes, foi observada uma melhora da função pulmonar após 3 a 4 meses de uso desse macrolídeo em dias alternados 62,63 . Baseado nesses resultados, a azitromicina tem sido recomendada por alguns autores para pacientes com BOPI 8 , embora não existam estudos que avaliem sua eficácia nesse grupo até o momento.…”
Section: Antibióticosunclassified